Annexin A6 Interacts With p65 and Stimulates NF‐κB Activity and Catabolic Events in Articular Chondrocytes. Issue 12 (27th November 2013) - Campbell, Kirk A.; Minashima, Takeshi; Zhang, Ying; Hadley, Scott; Lee, You Jin; Giovinazzo, Joseph; Quirno, Martin; Kirsch, Thorsten
Abstract : Objective: ANXA6, the gene for annexin A6, is highly expressed in osteoarthritic (OA) articular chondrocytes but not in healthy articular chondrocytes. This study was undertaken to determine whether annexin A6 affects catabolic events in these cells. Methods: Articular chondrocytes were isolated from Anxa6‐knockout mice, wild‐type (WT) mice, and human articular cartilage in which ANXA6 was overexpressed. Cells were treated with interleukin‐1β (IL‐1β) or tumor necrosis factor α (TNFα), and expression of catabolic genes and activation of NF‐κB were determined by real‐time polymerase chain reaction and luciferase reporter assay. Anxa6 −/− and WT mouse knee joints were injected with IL‐1β or the medial collateral ligament was transected and partial resection of the medial meniscus was performed to determine the role of Anxa6 in IL‐1β–mediated cartilage destruction and OA progression. The mechanism by which Anxa6 stimulates NF‐κB activity was determined by coimmunoprecipitation and immunoblot analysis of nuclear and cytoplasmic fractions of IL‐1β–treated Anxa6 −/− and WT mouse chondrocytes for p65 and Anxa6. Results: Loss of Anxa6 resulted in decreased NF‐κB activation and catabolic marker messenger RNA (mRNA) levels in IL‐1β– or TNFα‐treated articular chondrocytes, whereas overexpression of ANXA6 resulted in increased NF‐κB activity and catabolic marker mRNA levels. Annexin A6 interacted with p65, and loss of Anxa6 caused decreased nuclear translocation and retention of the active p50/p65 NF‐κB complex. Cartilage destruction in Anxa6 −/− mouse knee joints after IL‐1β injection or partial medial meniscectomy was reduced as compared to that in WT mouse joints. Conclusion: Our data define a role of annexin A6 in the modulation of NF‐κB activity and in the stimulation of catabolic events in articular chondrocytes.